Analysis of the springback phenomenon using finite element method - Tran, Tan Trung Le; Truong, Thien Tich (Vietnam Journal of Mechanics, 2024)
The springback phenomenon is a significant concern in manufacturing processes, particularly in metal component forming, as it directly affects dimensional control and the shape of formed parts. Accurate prediction and analysis of springback are crucial for achieving precise dimensional control and ensuring the desired final shape. Therefore, this study focuses on analyzing the springback phenomenon using finite element method. The primary objective is to develop a Matlab program for analyzing three-dimensional springback problems. Throughout the research process, the understanding of the phenomenon has been enhanced. The developed program has been successfully implemented to model and simulate the forming process, considering various aspects of the problem. The results of the solutions have been compared and evaluated, leading to important conclusions. The research also outlines future developments in this field. It is hoped that the results and understanding of this research will contribute to the field of computational mechanics and inspire further research.